Comportamento do maracujazeiro-amarelo (Passiflora edulis f. flavicarpa Deg.) submetido á diferentes formas de poda de formação - Coelho, Fernando Antonio Oliveira (2010)
The present work had the purpose of appraising the revenue of the yellow passion fruit , driven em observance the principals agroecologics , submitted the three forms different of conduct and pod. The I try was realized on Farm School of the Center of Sciences Agrarian from University State of the Maranhão into the period of february of 2009 the february of 2010. The statistical design used was entirely radomized with three treatments (T1, T2, T3) and five repetitions , identified in field for tapes colorful. The treatment T1 featured by absence of prunings , the treatment T2, featured by realization of prunings from the changes but also the height of the wire of support and the treatment T3, featured by realization of prunings but also the wire of support and prunings of formation. On area experimental have been chosen from interchangeably, fifteen plants of passion fruit being what five plants have been selects about to compose each treatment. The unity experimental was consist from one plant. The outcomes they showed what the treatment T1, where was not realized the pruning was higher in treatments T2 in number of produce and number of flowers , the one to in practice means that inside from the conditions what was realized the I try , isn't recommended the realization of prunings